Cardioneuroablation for cardioinhibitory vasovagal syncope. (27th April 2021) - John, Leah A.; Mullis, Andin; Payne, Joshua; Tung, Roderick; Aksu, Tolga; Winterfield, Jeffrey R.
Abstract: Background: Cardioneuroablation (CNA) is an emerging technique being used to treat patients with cardioinhibitory vasovagal syncope (VVS). We describe a case of CNA in targeting atrial ganglionated plexi (GP) based upon anatomical landmarks and fractionated electrogram (EGM) localization in a patient with cardioinhibitory syncope. Case Presentation: A 20‐year‐old healthy female presented with malignant VVS and symptomatic sinus pauses, with the longest detected at 10 s. She underwent acutely successful CNA with demonstration of vagal response (VR) noted after ablation of left sided GP, and tachycardia noted with right sided GP ablation. All GP sites were defined by anatomical landmarks and EGM analysis. By using the fractionation mapping software of Ensite Precision mapping system with high density mapping, fragmented EGMs were successfully detected in each GP site. One month after vagal denervation, there were no recurrent syncopal episodes or sinus pauses. Longer term follow‐up with implantable loop recorder is planned. Conclusion: We performed CNA in a patient with VVS by utilizing a novel approach of combined use of high density mapping and fractionation mapping software. With this approach, we were able to detect fractionation in all GP sites and demonstrate acute VR. This workflow may allow for a new, standardized technique suitable for widespread use.